2020
DOI: 10.21203/rs.3.rs-68522/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arterial Carboxyhemoglobin Levels In Covid-19 Critically Ill Patients

Abstract: Background : Oxidative stress conditions may be responsible for an up-regulation of the expression of heme oxygenase, the enzyme synthesizing carbon monoxide (CO) in cells. Elevated levels of arterial carboxyhemoglogin (CO-Hb) have been found in critically ill patients, including those suffering from acute lung injury. We aimed to investigate the changes of arterial CO-Hb levels in COVID-19 critically ill patients.Methods : A retrospective cohort study was conducted on the medical charts of 63 patients admitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The study selection process is shown in Figure 1a. For the case of COHb and COVID-19, 73 articles were retrieved from PubMed (n = 1) and Google Scholar (n = 72), one duplicate was removed and 68 articles were excluded after abstract review, leading to three articles that were finally included in the present study [20,24,25]. The study selection process is shown in Figure 1b…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study selection process is shown in Figure 1a. For the case of COHb and COVID-19, 73 articles were retrieved from PubMed (n = 1) and Google Scholar (n = 72), one duplicate was removed and 68 articles were excluded after abstract review, leading to three articles that were finally included in the present study [20,24,25]. The study selection process is shown in Figure 1b…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…For the case of the three studies concerning COHb and COVID-19, two were cross sectional studies [ 24 , 25 ] and one a case report [ 20 ]. Two of the studies were published in journals [ 20 , 25 ] and one on the preprint server Research Square (researchsquare.com) [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations